Interdisciplinarity at School: Challenges, Possibilities and Paths to a Transformative Educational Practice: DESAFIOS, POSSIBILIDADES E CAMINHOS PARA UMA PRÁTICA EDUCATIVA TRANSFORMADORA (REMUNOM, 2025)
This study focuses on the challenges faced in implementing interdisciplinarity in the school environment. It seeks to understand how this approach can contribute to a more integrated education, while analyzing the difficulties related to teacher training and the scarcity of resources in educational institutions. Using a qualitative methodology, with an emphasis on a literature review, the paper examines the main obstacles to interdisciplinary practice and proposes strategies for overcoming them. The results indicate that interdisciplinarity favors a more meaningful pedagogical practice, promoting the collective construction of knowledge. In addition, it is a transformative tool, capable of integrating knowledge and stimulating the development of critical and reflective skills, which are fundamental for a contextualized citizen's education.